2017
DOI: 10.3390/ijms18122534
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 in Vascular Wall Pathology: Unraveling Chronic Venous Insufficiency Pathophysiology

Abstract: Chronic venous insufficiency and varicose veins occur commonly in affluent countries and are a socioeconomic burden. However, there remains a relative lack of knowledge about venous pathophysiology. Various theories have been suggested, yet the molecular sequence of events is poorly understood. Transforming growth factor-beta one (TGF-β1) is a highly complex polypeptide with multifunctional properties that has an active role during embryonic development, in adult organ physiology and in the pathophysiology of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 131 publications
2
41
0
1
Order By: Relevance
“…Among the candidate genes, TGFBR1 were selected as a potential target. TGFBR1, a major component of the atherosclerotic process, is a specific TGF‐β receptor that mediates the physiological and pathological function of TGF‐β . TGFBR1 is critical for mediating the effects of TGF‐β‐induced on almost all cell types of cardiovascular system, including myofibroblasts, endothelial cells, and macrophages .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the candidate genes, TGFBR1 were selected as a potential target. TGFBR1, a major component of the atherosclerotic process, is a specific TGF‐β receptor that mediates the physiological and pathological function of TGF‐β . TGFBR1 is critical for mediating the effects of TGF‐β‐induced on almost all cell types of cardiovascular system, including myofibroblasts, endothelial cells, and macrophages .…”
Section: Discussionmentioning
confidence: 99%
“…TGFBR1, a major component of the atherosclerotic process, is a specific TGF-β receptor that mediates the physiological and pathological function of TGF-β. 22 TGFBR1 is critical for mediating the effects of TGF-β-induced on almost all cell types of cardiovascular system, including myofibroblasts, endothelial cells, and macrophages. 23 It has found that miR-130a-3p might play a critical role in negatively regulating HSC proliferation by directly targeting TGFBR1 via TGF-β/SMAD signaling pathway.…”
Section: Downregulated Expression Of Mir-27 In Myocardial Ischemia mentioning
confidence: 99%
“…Transforming growth factor-β is a family of cytokines participating in regulating growth and differentiation of cells (13). TGF-β1 was involved in various physiologic and pathologic conditions, which has many functions, including stimulating the proliferation and migration of VSMCs.…”
Section: Wall Shear Stress Regulates the Proliferation And Migration mentioning
confidence: 99%
“…Varicose veins often start from the lower extremities and are always diagnosed by physicians at a stage with clinical manifestations of oedema, engorging and tortuous veins, or venous ulceration. It affects more women than men in most populations . An early survey in Finland showed that the prevalence rates of physician‐diagnosed varicose veins were 25% in women and 7% in men .…”
Section: Introductionmentioning
confidence: 99%
“…An early survey in Finland showed that the prevalence rates of physician‐diagnosed varicose veins were 25% in women and 7% in men . However, reported prevalence rates varied remarkably in different studies, from less than 1% to 73% in women and 2% to 56% in men . The Finnish study identified risk factors such as age, body height, body mass index, standing at work, high socio‐economic status, and the numbers of births (in women) .…”
Section: Introductionmentioning
confidence: 99%